Towards Living Machines: current and future trends of tactile sensing, grasping, and social robotics. (23rd February 2023) - Vouloutsi, Vasiliki; Cominelli, Lorenzo; Dogar, Mehmet; Lepora, Nathan; Zito, Claudio; Martinez-Hernandez, Uriel
Abstract: The development of future technologies can be highly influenced by our deeper understanding of the principles that underlie living organisms. The Living Machines conference aims at presenting (among others) the interdisciplinary work of behaving systems based on such principles. Celebrating the 10 years of the conference, we present the progress and future challenges of some of the key themes presented in the robotics workshop of the Living Machines conference. More specifically, in this perspective paper, we focus on the advances in the field of biomimetics and robotics for the creation of artificial systems that can robustly interact with their environment, ranging from tactile sensing, grasping, and manipulation to the creation of psychologically plausible agents.